Geographic Information Systems: An Overview - Tang, Yang Tze (INTI Publishing House Sdn Bhd, 2005)
Geographic Information System (GIS) is an integrated information system that provides timely and quality spatial information for specific geographical applications. GIS ranges from a small piece of software programme to a highly complex and sophisticated integrated communications system. GIS is itself an integration of various specific subsystems. It also serves as an integration technology as it integrates knowledge from different disciplines and functions of various information technologies into one single system. GIS has been extensively used in government and private sectors for a number of scientific and non-scientific applications. Open GIS is the concept that provides inter-operability, extensibility and flexibility to this specific type of information system. This paper presents a generic definition of GIS from a broad perspective, the principal features and functions of GIS, and the application areas of GIS. The paper also includes a brief discussion on the integration technology concepts of GIS.